UNDERSTANDING LEARNERS: SOCIOLINGUISTIC PROFILES AND PEDAGOGICAL IMPLICATIONS (Web of Teachers: Inderscience Research, 2025)
This paper explores the sociolinguistic and sociocultural profiles of a group of bilingual learners in a rural public-school context, emphasizing the implications for effective language teaching and assessment. The study group comprises eighteen 13- to 14-year-old students from diverse cultural and linguistic backgrounds, primarily from transplant communities where Uzbek is spoken as a high-variety native language and Tajik is understood receptively. The learners also possess varying degrees of proficiency in Russian. The analysis distinguishes two learner subgroups based on their future use of English and motivational factors: one motivated by travel and career aspirations abroad, and another with more local or instrumental goals. Pedagogical implications focus on addressing learners’ sociolinguistic needs through exposure to different varieties of English and adapting teaching practices to reflect authentic language use. Additionally, the paper discusses how assessment practices should consider students’ linguistic backgrounds and communicative goals. This research highlights the importance of learner profiling in developing inclusive, context-sensitive language instruction that aligns with students’ sociocultural realities and aspirations.